Infographic: A journey around the COVID-19 vaccine for athletes - Rankin, A.; McLarnon, M. E. D.; Hull, J. H.; Gomes, C.; Heron, N. (Journal of Science and Cycling, 2021)
This infographic outlines considerations for athletes and their teams around vaccination against the SARS-CoV-2 (Covid-19) virus. There are currently three vaccines approved for use in the United Kingdom (UK); Pfizer/BioNTech, Moderna and Oxford/AstraZenica. It is important for athletes and their physicians to be aware of the potential side effects from any given COVID-19 vaccination, pros and cons of vaccination in a low-risk population, and the logistics of training around vaccination administration. Finally, education surrounding vaccination may help combat vaccine hesitancy in an athletic population.